Gases in the near-surface zone of the reclaimed Barycz municipal waste landfill – a case study from southern Poland - Kopera, Paulina A.; Sechman, Henryk; Twaróg, Anna (Geology, Geophysics and Environment, 2023)
The formation of biogas at municipal landfills and the significant emission of greenhouse gases from these facilities into the environment were the main reasons for analyzing the molecular composition of soil gas in the near-surface zone at the reclaimed part of the Barycz municipal waste landfill. The relations between the studied components (methane, carbon dioxide, light hydrocarbons and non-hydrocarbon components) and impact of the magnitude of recorded concentrations of methane and carbon dioxide on their emission to the atmosphere were evaluated. Two profiles were determined, along which 41 soil and landfill gas samples were taken at 20-meter intervals. At the same time, emissions were measured at each sampling point using a static chamber with a portable fluxometer. Chromatographic analysis showed that the concentrations of methane and carbon dioxide fluctuated in the ranges: 2.1 ppm – 76 vol% and 0.04 ppm – 11 vol%, respectively. Relatively high concentrations of these gases were determined at many of the measurement points, and this was particularly evident at the A-A’ profile, indicating stronger biochemical processes in this part of the landfill, or lateral migration of methane from the neighbouring stage II of the landfill, where biogas extraction is currently taking place. In addition, significant correlations between methane, carbon dioxide, and oxygen were demonstrated, indicating ongoing methane fermentation processes. Based on the study, it can be concluded that the southern part of the A-A’ profile is an optimal place to locate a degassing well from which biogas production could be used. However, the research is only preliminary and, it will be necessary to extend the soil gas tests before the final decision on the location of the well is made. Moreover, it has been shown that the concentrations of methane and carbon dioxide measured at points located outside the landfill were low. This means that generated biogas probably does not migrate beyond the boundaries of reclaimed waste landfill, but this will need to be confirmed by performing additional soil gas tests inside and outside the landfill area. The preliminary assessment of the effectiveness of the reclamation carried out was confirmed by the negligible values of the measured methane and carbon dioxide emissions on the surface.